SISTEM PENDUKUNG KEPUTUSAN DALAM MENENTUKAN SMKN BERPROGRAM STUDI TEKNOLOGI INFORMASI YANG FAVORIT BERDASARKAN PENDEKATAN ANALYTICAL HIERARCHY PROCESS (AHP) - Suryanto Suryanto (LPPM Universitas Bina Sarana Informatika, 2011)
To create a modern educational needs good IT foundation. But this is not something easy to be realized because of the problems of education in this country is not simple, as well as school of IT courses must resolve issues such as unavailability of a standard curriculum for schools that have IT courses, investment in schools which has a course IT is more expensive, is still at least schools that have IT courses, especially in East Jakarta municipality. These problems conducted this study with the objective of identifying the foundations of IT in the State Vocational High School IT / TKJ courses. In addition, this study also conducted a review of a decision support system in determining SMKN who have a favorite course of study IT. This needs to be done so that prospective students and parents / community can choose a SMKN who have a favorite course of study IT for children who can improve the skills and knowledge in accordance with the needs of the business, where in this study focused on High School SMKN 26, SMKN 22 and SMKN 24 under the auspices of the Department of Education and Culture (Department of P & K) East Jakarta. Technical analysis used in this research is Analytical Hierarchy Process (AHP), with an application Expert Choice 2000. The results of this study indicate that the top priority or the highest of three alternative strategic decision support in determining the SMKN who have a favorite course of study IT is to SMKN 26 with a weight value equal to 0.414 or 41.4% of the total specified alternative. Then the next alternative priority is the SMKN 22 (weight value 30.6%), and ranked the lowest priority is SMKN 24 (28% weighted value). Keywords: Decision support system, High School, Analytical Hierrachy Process.